Numerical Modelling of Steel Fibre Reinforced Concrete Subjected to Fatigue Loading - Mapfumo, Johnson Tatenda (Stellenbosch : Stellenbosch University, 2026)
Thesis (MEng)--Stellenbosch University, 2026.